Non-Alcoholic Fatty Liver Disease in Everyday Clinical Practice: From Diagnosis to Therapy - Marcin Kosmalski; Łukasz Mokros (Life)
Non-alcoholic fatty liver disease (NAFLD) is currently one of the most common hepatic disorders observed in daily medical practice [...]